2017
DOI: 10.3389/fneur.2017.00528
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Italian Version of the Dizziness Handicap Inventory, the Situational Vertigo Questionnaire, and the Activity-Specific Balance Confidence Scale for Peripheral and Central Vestibular Symptoms

Abstract: Neurophysiological measurements of the vestibular function for diagnosis and follow-up evaluations provide an objective assessment, which, unfortunately, does not necessarily correlate with the patients’ self-feeling. The literature provides many questionnaires to assess the outcome of rehabilitation programs for disequilibrium, but only for the Dizziness Handicap Inventory (DHI) is an Italian translation available, validated on a small group of patients suffering from a peripheral acute vertigo. We translated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…The Slovenian DHI had excellent test-retest reliability based on the intraclass correlation coefficient. This is consistent with other studies (32,56). Since the NVI has only recently been developed, to the best of our knowledge no studies have yet been published regarding its test-retest reliability (35,57).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Slovenian DHI had excellent test-retest reliability based on the intraclass correlation coefficient. This is consistent with other studies (32,56). Since the NVI has only recently been developed, to the best of our knowledge no studies have yet been published regarding its test-retest reliability (35,57).…”
Section: Discussionsupporting
confidence: 92%
“…According to Cronbach's alpha, the Slovenian DHI, NVI and THI had perfect internal consistency, even higher compared to other studies (7,8,32). The Slovenian COMQ-12 had acceptable internal consistency.…”
Section: Discussionmentioning
confidence: 70%
“…The literature data are equivocal. Colnaghi et al [11] found the relationships between age and the DHI total, and DHI subscales as well, whereas Tamber et al [5] did not find any such correlations in spite of [5]. However, in the present study yes/no categories were produced by adding "sometimes" and "yes" answers from a 3-pts scale, while Tamber et al used a 6-pts scale and added scores 0−1 and 2−6.…”
Section: Discussioncontrasting
confidence: 55%
“…It is particularly interesting that ABC scores showed significant improvement because such a self-report questionnaire is a reliable index of global risk of fall in everyday activities with regard to other clinical questionnaires such as DHI and DGI, respectively, focusing on perceived dizziness and gait analysis evaluation. 52 This study suffers from some limitations. First, the sample size needs to be increased in order to reach more reliable conclusions about the relation between stapes surgery and improvements in balance and daily life outcomes.…”
Section: Discussionmentioning
confidence: 98%